An Endoplasmic Reticulum Stress–MicroRNA‐26a Feedback Circuit in NAFLD. Issue 4 (6th November 2020) - Xu, Haixia; Tian, Yan; Tang, Dongmei; Zou, Sailan; Liu, Geng; Song, Jiulin; Zhang, Guixiang; Du, Xiao; Huang, Wei; He, Bin; Lin, Weiqiang; Jin, Liang; et al.
Abstract : Background and Aims: Endoplasmic reticulum (ER) stress is an adaptive response to excessive ER demand and contributes to the development of numerous diseases, including nonalcoholic fatty liver disease (NAFLD), which is hallmarked by the accumulation of lipid within hepatocytes. However, the underlying mechanisms remain elusive. MicroRNAs (miRNAs) play an indispensable role in various stress responses, but their implications in ER stress have not yet been systemically investigated. In this study, we identify a negative feedback loop consisting of hepatic ER stress and miR‐26a in NAFLD pathogenesis. Approach and Results: Combining miRNA dot blot array and quantitative PCR, we find that miR‐26a is specifically induced by ER stress in liver cells. This induction of miR‐26a is critical for cells to cope with ER stress. In human hepatoma cells and murine primary hepatocytes, overexpression of miR‐26a markedly alleviates chemical‐induced ER stress, as well as palmitate‐triggered ER stress and lipid accumulation. Conversely, deficiency of miR‐26a exhibits opposite effects. Mechanistically, miR‐26a directly targets the eukaryotic initiation factor 2α, a core ER stress effector controlling cellular translation. Intriguingly, miR‐26a is reduced in the livers of patients with NAFLD. Hepatocyte‐specific restoration of miR‐26a in mice significantly mitigates high‐fat diet–induced ER stress and hepatic steatosis. In contrast, deficiency of miR‐26a in mice exacerbates high‐fat diet–induced ER stress, lipid accumulation, inflammation and hepatic steatosis. Conclusions: Our findings suggest ER stress–induced miR‐26a up‐regulation as a regulator for hepatic ER stress resolution, and highlight the ER stress/miR‐26a/eukaryotic initiation factor 2α cascade as a promising therapeutic strategy for NAFLD.